The Influence of Promotion and Prevention Models in Preventing Psychosocial Problems in Nurses at Medan City Hospital - Sri Eka Wahyuni; Wardiyah Daulay; Mahnum Lailan Nasution; Jenny Marlindawani Purba (Poltekkes Kemenkes Surakarta, 2026)
Background: Psychosocial problems experienced by nurses when working in hospitals. Promotion Model Mental Health Promotion and Prevention is a solution that can be offered to prevent psychosocial problems in nurses. The aim of this study is to identify the influence of the promotion and prevention model on the prevention of psychosocial problems among nurses at Medan City Hospital. Methods: Quasi-experimental research design with a control group. The study was conducted on nurses at one of the hospitals in Medan City with a sample of 100 nurses, with details of 50 nurses in the intervention group and 50 nurses in the control group taken using purposive sampling. The research instrument used GAD-7. The intervention provided was a mental health promotion and prevention model (stress management training and self-help group therapy). Data were analyzed using the Wilcoxon Signed-Rank Test to assess within-group differences and the Mann–Whitney U Test to compare post-intervention anxiety levels between the intervention and control groups. Results: The study showed that there was a statistically significant difference in the level of anxiety of nurses after the intervention. There was a significant reduction in anxiety levels among nurses following the implementation of the mental health promotion and prevention model in the intervention group (p = 0.001). Conclusion: It was concluded that the intervention was significantly effective in reducing the anxiety levels of nurses at Medan City Hospital. This mental health promotion and prevention model can be implemented to prevent psychosocial problems early in healthcare workers.